PENGARUH PEMBERIAN SOLID KELAPA SAWIT DAN FOSFOR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG (Solanum melongena L.) - Susi Mayasari Magdalena Simatupang; Husna Yetti; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this studyis to determine the effect of the interaction of solid germination of palm oil and phosphorus fertilizer and get the best dose on the growth and yield of eggplant. The experiment was conducted at Experimental Garden of Agriculture Faculty of Riau University in September - December 2017 in the form of 3x3 factorial experiment arranged according to RAL where the first factor of Solid Palm oil dose (17, 34 and 51 ton.ha-1) second factor dose of TSP fertilizer (0, 75 and 150 kg.ha-1). The parameters observed were plant height, flowering age, age of first harvest, number of fruits per plant, fruit length, fruit diameter and fruit weight per plant. The data obtained were analyzed statistically using variance then the results obtained were followed by Duncan's multiple-range test of 5%. The results showed that solid grading of oil palm and TSP fertilizer had significant effect on all parameters except the age of flowering and the number of fruit crops. Giving solid of oil palm have real effect on all parameters except fruit diameter whereas TSP giving no significant effect on all parameters except the age of first harvest and weight of fruit per plant. Solid palm oil 34 ton.ha-1 and TSP 75 kg.ha-1 give the best results on the growth and yield of eggplant. Keywords: eggplant, solid palm oil and TSP fertilizer